Sick building syndrome and stress among office workers. - Ritwichai , A.; Buathong, N. (Chulalongkorn Medical Journal, 2023)
Background : Sick building syndrome (SBS) is defined with non – specific symptoms among office workers of certain buildings. Many of the symptoms seem to be associated with environmental and psychosocial factors at the workplace. However, the association between SBS and stress has not been studied in Thailand. Objectives : To estimate the prevalence of SBS and stress among office workers and to determine the association between SBS and stress their related factors. Methods : Data were obtained from the office workers at SM Tower office building from July to October 2014. A total of 273 participants were recruited. Participants completed four questionnaires regarding to demographic characteristic, environmental in working condition, SBS questionnaires and Suanprung Stress Test-20 (SPST - 20), the data were analyzed using percentage, mean, standard deviation, chi-square test and multiple logistic regression. Results : The prevalence of SBS was 37.4%. The prevalence of mild, moderate, high and severe stress status were 11.4, 29.3, 44.3 and 15.0 percent respectively. In multivariate analysis, the statistically significant factors with SBS were severe stress status (OR = 4.90, 95%CI = 1.55 - 15.48), duration of using computer more than 8 hours per day (OR = 2.53, 95%CI = 1.28 - 5.00), materials of office flooring from PVC or plastic (OR = 2.13, 95%CI = 1.15 - 3.95), and using the effluvium office equipment such as correcting fluid and glue (OR = 1.97, 95%CI = 1.09 - 3.57). Conclusion : The occupational health and safety unit should emphasize not only the conditions of safe and healthy environmental factors in the office building but also the strategies for coping with stress of the office workers in order to reduce the SBS and to promote the quality of life among them.